(untitled) (Journal of Business and Technology (Dhaka), 2015)
This paper is dealing with womens entrepreneurial activities according to socio-economic aspects and the factors affecting their developments. Here, micro-entrepreneurship is focused mainly. Women micro-entrepreneurs are now holding a large number of enterprises creating employment, fastening the speed of economic growth and making social empowerment. In-spite of the significant role-played, their position in many areas of Bangladesh leaves much to be desired. This study aims to provide a micro-level perspective of different challenges faced by women micro-entrepreneurs in the Bangladeshi socioeconomic context and their future prospects. The study adopted a selfadministered questionnaires and interviews with women micro-entrepreneurs engaged in diverse sectors. The findings show that Bangladeshi women microentrepreneurs face an unfavorable business environment that is characterized by various challenges ranging from low technical, administrative and government support, lack of scope of professional development and bad interpersonal relationship. The findings also highlight the socio-economic characteristics such as age, marital status, educational status and starting age of business. We have found that married and above 25 years women are more likely to be micro-entrepreneurs. They do not get proper training but the government is being more positive in this regard, as they can get the loan easily. Hence, with family as well as government support they are becoming empowered day by day DOI: http://dx.doi.org/10.3329/jbt.v9i1.22778 Journal of Business and Technology (Dhaka) Vol.9(1) 2014; 53-70